2014
DOI: 10.1002/app.40560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different polymerization protocols on the degree of conversion of two dual‐cured core buildup composites polymerized by light‐emitting diode and halogen light‐curing units

Abstract: The aim of study was to investigate the effects of various curing protocols with quartz–tungsten halogen (QTH) or light‐emitting diode (LED) light‐curing units on the degree of conversion (% DC) of two dual‐cured core buildup resin composites. Two dual‐cured core buildup resin composites, Clearfil Dc Core Automix (CLF) and Grandio Core Dc (GR), were selected. Specimens were exposed to the polymerization protocols as follows: there was immediate photoactivation or photoactivation delayed by 2 or 5 min by a QTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(137 reference statements)
0
1
1
Order By: Relevance
“…The Knoop hardness values for Fluorocore 2+ are similar to those reported by Arrais et al, 15 slightly more than those reported by Tauböck et al in regards to Multicore Flow, 44 and similar to those reported for Rebilda DC tooth colored material. 44 Clearfil DC Core values in this study approximate those published by Yoshida and Meng 10 but are less than those reported by Karakis et al 11 In regards to the dual cure core material self-cure results, this study contrasts those described by Tauböck et al, 6 Schmage et al, 11 and Karakis et al 39 Some variance could be related to different curing regimens and specimen thickness variations. However, these differences cannot be fully explained at this time and can be the subject for future studies.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The Knoop hardness values for Fluorocore 2+ are similar to those reported by Arrais et al, 15 slightly more than those reported by Tauböck et al in regards to Multicore Flow, 44 and similar to those reported for Rebilda DC tooth colored material. 44 Clearfil DC Core values in this study approximate those published by Yoshida and Meng 10 but are less than those reported by Karakis et al 11 In regards to the dual cure core material self-cure results, this study contrasts those described by Tauböck et al, 6 Schmage et al, 11 and Karakis et al 39 Some variance could be related to different curing regimens and specimen thickness variations. However, these differences cannot be fully explained at this time and can be the subject for future studies.…”
Section: Discussioncontrasting
confidence: 46%
“…36,37 Accordingly, mixed reports exist concerning the self-cure performance of resin composite dual-cure materials. Studies have reported that resin dual-cure cement materials may not reach similar degree of polymerization when evaluated in the absence of light activation, 38,39 contrasted by other works providing evidence that some dual-cure core materials have similar self-cure mode curing as that observed with photopolymerization. 6,11 Under the conditions of this study, no product under self-cure conditions attained similar hardness to that observed of the photopolymerized top surface of the same product.…”
Section: Discussionmentioning
confidence: 92%